Online Book Trade in Siberia and the Far East - O. N. Alshevskaya (Библиосфера, 2021)
The article analyzes the activities of regional Internet companies offering books in Siberia and the Far East. The research methodology is based on the combination of comparative-typological analysis and landscape-reconstructing approach. Use is made of monitoring results of bookselling enterprises in the region within the framework of the federal project “Cultural Map of Russia”. It is shown that online sales are a dynamically developing channel of the traditional (printed) retail book market in Russia. Based on the identification and analysis of the main characteristics of enterprises offering books on the Internet (location, subject of the Russian federation, assortment, degree of integration, structure of the enterprise, etc.), the most common groups of enterprises in the regional book market are identified: internet divisions of publishing houses; multi-profile online stores; online book stores without retail divisions; online stores of bookselling enterprises. As the most common type in the regional market, the Internet divisions of wholesale and retail independent and online bookselling enterprises are identified. The features of the presentation of a specialized book on the Internet are revealed. The main areas of specialization of federal, regional and local companies offering book products on the Internet along with other products are identified: educational and office supplies, educational games and toys, business and technical literature, etc. The trends and promising directions of development of the regional online book trade are revealed. Diversification of activities and multichannel are defined as the key trend in the development of the regional book market.